2019
DOI: 10.33545/gynae.2019.v3.i2b.12
|View full text |Cite
|
Sign up to set email alerts
|

Study of etiopathology and risk factors of postpartum haemorrhage in a tertiary care center

Abstract: Background: Postpartum haemorrhage (PPH) is one of the most common causes of maternal morbidity and mortality throughout the world. PPH significantly leads to anaemia, infection, lactional failure, blood transfusion and psychological morbidity. Pregnancy and childbirth involves significant health risks, even to women with no preexisting health problem. The objective of this study was to analyse different causes and risk factors for postpartum haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a similar study done by Yogesh et al on acceptance of post-abortal contraception, it was found that 64 (16%) cases had barriers to contraception (condom), 52 (13%) cases had pills, 70 (17.5%) cases had IUCD, 106 (26.5%) cases had a permanent method, 48 (12%) cases had injectable contraception and 60 (15%) had no method of contraception use. 2,9 Acceptance of post-abortal contraception was 85%. Overall acceptance of contraception was higher than in our study and preferred methods also varied.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study done by Yogesh et al on acceptance of post-abortal contraception, it was found that 64 (16%) cases had barriers to contraception (condom), 52 (13%) cases had pills, 70 (17.5%) cases had IUCD, 106 (26.5%) cases had a permanent method, 48 (12%) cases had injectable contraception and 60 (15%) had no method of contraception use. 2,9 Acceptance of post-abortal contraception was 85%. Overall acceptance of contraception was higher than in our study and preferred methods also varied.…”
Section: Discussionmentioning
confidence: 99%